1999
DOI: 10.1073/pnas.96.7.3963
|View full text |Cite
|
Sign up to set email alerts
|

Loss of transformed phenotype in cancer cells by overexpression of the uteroglobin gene

Abstract: Uteroglobin (UG) is a multifunctional, secreted protein that has receptor-mediated functions. The human UG (hUG) gene is mapped to chromosome 11q12.2-13.1, a region frequently rearranged or deleted in many cancers. Although high levels of hUG expression are characteristic of the mucosal epithelia of many organs, hUG expression is either drastically reduced or totally absent in adenocarcinomas and in viral-transformed epithelial cells derived from the same organs. In agreement with these findings, in an ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…Animals-UG-KO mice were generated by targeted disruption of the UG gene in embryonic stem cells as described previously (18). Both UG-KO mice and their WT littermates were maintained under germ-free conditions, and all of the experiments were performed according to a protocol approved by the institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals-UG-KO mice were generated by targeted disruption of the UG gene in embryonic stem cells as described previously (18). Both UG-KO mice and their WT littermates were maintained under germ-free conditions, and all of the experiments were performed according to a protocol approved by the institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…It is constitutively expressed in the lungs of all mammals, and targeted disruption of the UG gene in mice (16) increases susceptibility to pulmonary inflammation (17). Moreover, we (18) and others (19) have previously demonstrated that overexpression of UG in cancer cells reverses their transformed phenotype and neoplastic potential. We also demonstrated that UG-knock-out (UG-KO) mice (16) are highly susceptible to lung tumorigenesis by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, a carcinogen in cigarette smoke (20).…”
mentioning
confidence: 99%
“…The tumor tissues were homogenized; lysed in lysis buffer composed of 50 mM Tris-HCl (pH 7.5) containing 150 mM NaCl, 1% Nonidet P-40, 15 g/ml leupeptin, and 0.5 mM phenylmethylsulfonyl fluoride; and centrifuged at 12,000 ϫ g for 10 min. The clear supernatants were collected, and MMP-2 expression was detected by Western blot analysis (32). Briefly, the sample containing an equal amount of total proteins was resolved by SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Higher expression of uteroglobin and follistatin-like 1 in dysregulated non-receptive endometrium is likely to reflect the pro-inflammatory type of endometrial response that has been documented following early luteal mifepristone treatment (Ghosh et al 1996, 1997, Sengupta et al 2003, Miyamae et al 2006. Furthermore, it would be interesting to explore whether so-called tumour suppressor-like action of uteroglobin (Zhang et al 1999) has any bearing on endometrial receptivity and hostility.…”
Section: Implantation-stage Endometrial Transcript Profilesmentioning
confidence: 99%